2017
DOI: 10.1186/s13287-017-0727-7
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell-derived extracellular vesicles for kidney repair: current status and looming challenges

Abstract: Novel therapies are urgently needed to address the rising incidence and prevalence of acute kidney injury (AKI) and chronic kidney disease (CKD). Mesenchymal stem/stromal cells (MSCs) have shown promising results in experimental AKI and CKD, and have been used in the clinic for more than a decade with an excellent safety profile. The regenerative effects of MSCs do not rely on their differentiation and ability to replace damaged tissues, but are primarily mediated by the paracrine release of factors, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
107
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(114 citation statements)
references
References 70 publications
(74 reference statements)
1
107
0
Order By: Relevance
“…Collectively, these observations suggest that EVs produced by Lean‐MSCs might mitigate cellular injury by modulating multiple reparative pathways. Current evidence suggests that MSC possess potent immunomodulatory properties that are primarily mediated by the release of EVs , which carry anti‐inflammatory elements in the form of genes, proteins, and microRNAs . Furthermore, we have recently shown that knocking down the anti‐inflammatory gene IL‐10 in MSC‐derived EVs blunts their capacity to repair the poststenotic kidney, implying that the salutary effects of EVs are mediated by their anti‐inflammatory cargo .…”
Section: Discussionmentioning
confidence: 92%
“…Collectively, these observations suggest that EVs produced by Lean‐MSCs might mitigate cellular injury by modulating multiple reparative pathways. Current evidence suggests that MSC possess potent immunomodulatory properties that are primarily mediated by the release of EVs , which carry anti‐inflammatory elements in the form of genes, proteins, and microRNAs . Furthermore, we have recently shown that knocking down the anti‐inflammatory gene IL‐10 in MSC‐derived EVs blunts their capacity to repair the poststenotic kidney, implying that the salutary effects of EVs are mediated by their anti‐inflammatory cargo .…”
Section: Discussionmentioning
confidence: 92%
“…Various studies have also provided evidence that MSC‐derived exosomes are crucial cardioprotective agents: They can reduce not only infarct size but also cardiomyocyte apoptosis (Barile et al, ; Lai et al, ). Of note, the beneficial effects of MSC‐derived exosomes are not limited to cardiac regeneration, the therapeutic effects similar to cardioprotective ones can also be obtained in the form of alleviation of acute lung injury (Khatri, Richardson, & Meulia, ; promotion of lung, kidney, or brain injury repair (Aghajani Nargesi, Lerman, & Eirin, ); and acceleration of wound healing (Liu, Wang, & Wang, ). Exosomes and their microRNAs are regarded as critical players in bone regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…For therapeutics, there is increasing evidence implicating the renoprotective role of exosomes, particularly those derived from MSCs, for attenuation and/or prevention of AKI (Aghajani Nargesi et al, 2017). Administration of extracellular vesicles derived from human Wharton's jelly MSCs could decrease renal injury and improve renal function after ischemia/ reperfusion-induced renal damage in rats (Zhang et al, 2014;Zhang et al, 2016).…”
Section: Acute Kidney Injurymentioning
confidence: 99%